Pengaruh Non Perfoming Loan (NPL) Dan Loan To Deposit Ratio (LDR) Terhadap Profitabilitas Pada Bank Konvensional Di Indonesia - Pramesti Setianingrum; Selly Puspitasari (Departement of Mathematics Education, 2023)
This research is motivated by conventional commercial bank financial ratios that are used to measure bank financial performance and profitability at conventional commercial banks themselves. This study uses a quantitative approach using panel data analysis which aims to determine the effect of Net Performing Loans (NPL) and Loan To Deposit Ratio (LDR) on Return On Assets (ROA). The data source used is secondary data. The data collection method is done by means of documentation and content analysis. The results of this study indicate that the Net Performing Loan (NPL) ratio has a negative effect on Return On Assets (ROA) at conventional commercial banks for the period 2017 Quarter I to 2021 Quarter IV, the Loan To Deposit Ratio (LDR) ratio has a positive effect on Return On Assets (ROA) ) in conventional commercial banks for the period 2017 Quarter I to 2021 Quarter IV.